2018
DOI: 10.1002/cbdv.201800090
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay‐Guided Isolation of Antifungal Compounds from Disporopsis aspersa (Hua) Engl. ex Diels against Pseudoperonospora cubensis and Phytophthora infestans

Abstract: Oomycetes are one type of the most highly destructive of the diseases that cause damage to some important crop plants, such as potato late blight, cucumber downy mildew, and grape downy mildew. As main approach of the ongoing search for new botanical fungicide from plant, the secondary metabolites of D. aspersa were investigated. Through efficient bioassay-guided isolation, two new (1 and 2) and 12 known compounds (3 - 14) were isolated, and their structures were determined via extensive NMR, HR-ESI-MS, and IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Disporopsis aspera is a perennial herb of Disporopsis genus of Liliaceae, and its rhizomes are used as medicine in traditional remedies, having the functions of easing thirst, nourishing yin and moistening. In our previous work, we first reported that crude extracts from D. aspera exhibited excellent antifungal activity, and isolated l ‐pyroglutamic acid has preferable control effects on Pseudoperonospora cubensis and Phytophthora infestans 18 . In this study, we found that the crude extract of the rhizomes of D. aspera exhibited effective antifungal activity against Podosphaera xanthii .…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Disporopsis aspera is a perennial herb of Disporopsis genus of Liliaceae, and its rhizomes are used as medicine in traditional remedies, having the functions of easing thirst, nourishing yin and moistening. In our previous work, we first reported that crude extracts from D. aspera exhibited excellent antifungal activity, and isolated l ‐pyroglutamic acid has preferable control effects on Pseudoperonospora cubensis and Phytophthora infestans 18 . In this study, we found that the crude extract of the rhizomes of D. aspera exhibited effective antifungal activity against Podosphaera xanthii .…”
Section: Introductionmentioning
confidence: 64%
“…Our prior work revealed that L-pyroglutamic acid and salicylic acid isolated from D. aspera showed promising antifungal activity against Phytophthora infestans and Pseudoperonospora cubensis. 18 In this work, we reported that D. aspera rhizomes extract has excellent inhibitory activity against Podosphaera xanthii and L-Aze was isolated and identified as the main active substance from the extract of D. aspera rhizome.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that purified pyroglutamic acid exhibits antibacterial properties against Bacillus and Enterobacter strains, as well as antifungal activity against phytopathogens (Huttunen, Noro, & Yang, 1995;F. Zhu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Pyroglutamic acid is a potential precursor of glutamate, which is essential for the first step in the de novo biosynthesis of the antioxidant glutathione (Forman, Zhang, & Rinna, 2009; Kumar & Bachhawat, 2012). Previous studies have shown that purified pyroglutamic acid exhibits antibacterial properties against Bacillus and Enterobacter strains, as well as antifungal activity against phytopathogens (Huttunen, Noro, & Yang, 1995; F. Zhu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is known as a powerful antioxidant [33]. Previous studies have shown that l -pyroglutamic acid exhibits both antibacterial [34] and antifungal activity against phytopathogenic Pseudoperonospora cubensis and Phytophthora infestans [35]. To the best of our knowledge, there are no reports characterizing the impact of this compound on Fusaria.…”
Section: Introductionmentioning
confidence: 99%